Omotenashi Concept in Japanese Expression in Hospitality - Uning Kuraesin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Excellent service is a very important element in Japanese business. Optimal and excellent service is the goal of a service product provided to customers. One of the industries engaged in the service business is hospitality. Hospitality services require a high level of hospitality, and in Japan this level of hospitality is very important. In Japanese culture it is famous for Omotenashi which means hospitality. Omotenashi is a culture of providing the best meals and services to guests through karmic manners that are done wholeheartedly. Omotenashi, which has its roots in the cha no yu ceremony in Japan, has become a form of local wisdom that has developed in the service industry today. In the hospitality industry, one form of Omotenashi is the use of polite language (Keigo) in providing waiters to guests. This study takes data from examples of expressions used in hospitality when welcoming guests. The polite language (Keigo) used is Kenjogo which is mostly used by receptionists, then Sonkeigi, and the form of Teineigo. The use of these language expressions contains the concept of Omotenashi, which means that friendly service will make guests feel comfortable and feel satisfied with hotel services. Hotel maids provide services without expecting any reward and are done wholeheartedly to maintain the reputation of the hotel, so that guests can end up coming back.